Bearing capacity of driven pile and determination of inhomogeneous mudstone around the pile - Zhang, Yamei; Sun, Gan; Bai, Xiaoyu; Sang, Songkui; Han, Jianyong; Yan, Nan; Zhang, Mingyi; Gao, Xiaodong; Li, Weiqi (Frontiers in Earth Science, 2023)
Whether the heterogeneity of mudstone foundation leads to abnormal bearing capacity of driven pile has always been discussed. The paper introduces the standard penetration test hammering number and needle penetration strength for quantitative analysis by macroscopic observation of the engineering field on the mudstone stratum self-structure and microscopic observation by simple and feasible electronic magnification. According to the analysis of typical engineering examples, it is found that the abnormal bearing capacity of piles in mudstone stratum is related to mudstone heterogeneity. The method of evaluating mudstone uniformity by heterogeneous index η is proposed, when η>2, the engineering measures should be taken. The paper's work can provide assistance in determining a reasonable solution to the problem of abnormal bearing capacity at driven piles in mudstone foundations.